VD_FINDINFO Décision / 2013 / 501 vom 10. April 2013 - VD Tribunal cantonal (2013)
ABUS D'AUTORITÉ, LÉSION CORPORELLE SIMPLE, POLICE, LOI SUR LA POLICE, TRANSPORT | 123 CP, 14 CP, 312 CP, 319 al. 1 CPP (CH)